2002
DOI: 10.1093/jexbot/53.368.415
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ethylene receptor protein Cm‐ERS1 during fruit development in melon (Cucumis melo L.)

Abstract: Antibodies against melon ethylene receptor, Cm- ERS1 was prepared. Cm-ERS1 protein formed a disulphide-linked homodimer and it was present in microsomal membranes but not in soluble fractions. Cm-ERS1 protein was present at high levels in melon fruit during early developmental stages. This transition pattern was also observed in another melon cultivar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 30 publications
4
17
0
Order By: Relevance
“…The predicted polypeptide has a deduced molecular mass of 70.013 kDa. The predicted value is similar to the ethylene receptors ERS1 (68 kDA) from Arabidopsis (Hall et al, 2000), Cm-ERS1 (75 kDA) from melon (Takahashi et al, 2002) and Nt-ERS1 (70 kDA) from tobacco (Terajima et al, 2001).…”
Section: Generation and Sequence Analysis Of Eger D3supporting
confidence: 66%
“…The predicted polypeptide has a deduced molecular mass of 70.013 kDa. The predicted value is similar to the ethylene receptors ERS1 (68 kDA) from Arabidopsis (Hall et al, 2000), Cm-ERS1 (75 kDA) from melon (Takahashi et al, 2002) and Nt-ERS1 (70 kDA) from tobacco (Terajima et al, 2001).…”
Section: Generation and Sequence Analysis Of Eger D3supporting
confidence: 66%
“…The Cys-4 and Cys-6 residues are conserved in all ethylene receptors, and the N termini of the five receptors have high amino acid identity. Evidence indicates that ethylene receptors can form homodimers in plants (15,39), but the presence of heterodimers between ethylene receptors has not been demonstrated.…”
Section: Formation Of Heterodimers By Etr1 and Ers2 When Transgenicalmentioning
confidence: 99%
“…Due to distinct anatomical, reproductive and developmental features, the melon fruit developmental stages are categorized into ethylene sensitive and ethylene insensitive stage with the developing fruit having lower affinity to ethylene than the ripening fruit. 143,144 During fruit ripening in muskmelon, Cm-ERS1 transcript level increased slightly in the pericarp of fruit. Also there was a concomitant increase in Cm-ETR1 transcripts along with climacteric ethylene production.…”
mentioning
confidence: 99%
“…103 Studies performed to examine the temporal and spatial expression pattern of Cm-ERS1 protein, during fruit development, revealed that a posttranscriptional regulation of Cm-ERS1 expression affects stage and tissue-specific accumulation of the protein. 144 The melon subfamily II ethylene receptor, Cm-ETR2 mRNA, exhibits earlier accumulation compared with Cm-ETR1 during ripening, and its transcript accumulation increased during melon ripening, and declined in parallel with a reduction in ethylene production.…”
mentioning
confidence: 99%